Access to preemptive registration on the waiting list for renal transplantation: a hierarchical modeling approach. (28th April 2015) - Riffaut, Natacha; Lobbedez, Thierry; Hazzan, Marc; Bertrand, Dominique; Westeel, Pierre‐François; Launoy, Guy; Danneville, Isabelle; Bouvier, Nicolas; Hurault de Ligny, Bruno
Summary Preemptive kidney transplantation is associated with both longer patient and graft survival. This study was carried out to estimate the association between the renal units and preemptive registration on the waiting list for first deceased donor renal transplantation in a French network of care. From 2008 to 2012, 1529 adult patients followed in 48 units of the French North‐West network and registered on the waiting list for a first deceased donor renal allograft were included. We used a mixed logistic regression with renal units as random‐effects term for statistical analysis. Of the 1529 patients included, 407 were placed on the waiting list preemptively. There was a significant variability across renal units (variance 0.452). In multivariate analysis, factors independently associated with preemptive registration were cardiovascular disease (odds ratio (OR) 0.57, [95% CI: 0.42–0.79]), social deprivation (OR 0.73, [95% CI 0.57–0.94]), and renal units' characteristics (ownership of the facility: academic hospital, reference—community hospital, OR 0.44, [95% CI 0.24–0.80]—private hospital, OR 0.35, [95% CI 0.18–0.69] and transplant center; P < 0.10]. Variability between renal units was reduced after taking into account their characteristics but was not influenced by patient characteristics. Preemptive registration is associated with renal units, transplant centers, and social deprivation and can be partly explained by disparities in practices.